Decolonising the Map Through Literary Cartography in Select Malayalam Novels - Sethuparvathy, S; Jha, Smita (SARE: Southeast Asian Review of English, 2024)
Using select indigenous novels translated from the Malayalam language, this paper will study how fictional spaces created by writers of Indian regional languages become a counter-narrative for colonial history and decolonise narrative and physical spaces. The paper will examine how postcolonial texts become ethnographic and social commentaries on colonial binaries and become resistance narratives to the hegemonic powers. Questions like how regional writers decolonise occidental maps, how the authors write alternative histories, how different versions of postcolonial communities are portrayed, how a postcolonial nation-state is built through literature, how communities that were left out in colonial discourses are brought back to the folds; how the history of a place influences power and identity of people; how Malayali writers locate an imagined space within actual geographic space through cartography; what determines the boundaries of these spaces- economically, culturally, historically, and politically, etc. will be addressed.